PEGylated PAMAM dendrimer–doxorubicin conjugate-hybridized gold nanorod for combined photothermal-chemotherapy - Li, Xiaojie; Takashima, Munenobu; Yuba, Eiji; Harada, Atsushi; Kono, Kenji (Biomaterials, 2014)
We prepared pH-sensitive drug–dendrimer conjugate-hybridized gold nanorod as a promising platform for combined cancer photothermal-chemotherapy under in vitro and in vivo conditions. Poly(ethylene glycol)-attached PAMAM G4 dendrimers (PEG–PAMAM) were first covalently linked on the surface of mercaptohexadecanoic acid-functionalized gold nanorod (MHA-AuNR), with subsequent conjugation of anti-cancer drug doxorubicin (DOX) to dendrimer layer using an acid-labile-hydrazone linkage to afford PEG–DOX–PAMAM–AuNR particles. The particles with a high PEG–PAMAM dendrimer coverage density (0.28 per nm2 AuNR) showed uniform sizes and excellent colloidal stability. In vitro drug release studies demonstrated that DOX released from PEG–DOX–PAMAM–AuNR was negligible under normal physiological pH, but it was enhanced significantly at a weak acidic pH value. The efficient intracellular acid-triggered DOX release inside of lysosomes was confirmed using confocal laser scanning microscopy analysis. Furthermore, the combined photothermal-chemo treatment of cancer cells using PEG–DOX–PAMAM–AuNR for synergistic hyperthermia ablation and chemotherapy was demonstrated both in vitro and in vivo to exhibit higher therapeutic efficacy than either single treatment alone, underscoring the great potential of PEG–DOX–PAMAM–AuNR particles for cancer therapy.